1998
DOI: 10.1111/0022-1082.00066
|View full text |Cite
|
Sign up to set email alerts
|

Costly Search and Mutual Fund Flows

Abstract: This paper studies the f lows of funds into and out of equity mutual funds. Consumers base their fund purchase decisions on prior performance information, but do so asymmetrically, investing disproportionately more in funds that performed very well the prior period. Search costs seem to be an important determinant of fund f lows. High performance appears to be most salient for funds that exert higher marketing effort, as measured by higher fees. Flows are directly related to the size of the fund's complex as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

214
2,187
19
27

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,850 publications
(2,447 citation statements)
references
References 33 publications
214
2,187
19
27
Order By: Relevance
“…We observe that our model captures the convexity of the flow-performance relationship identified empirically by Ippolito (1992), and Sirri and Tufano (1998). 8 This relationship is generally regarded as an exogenous feature of the interaction between mutual funds and their investors, and is typically interpreted as evidence that investors contribute enthusiastically to funds that have performed well, but hesitate to withdraw their investments from funds that have performed poorly.…”
Section: G the Relationship Between The Investor's Allocation And Idsupporting
confidence: 54%
See 1 more Smart Citation
“…We observe that our model captures the convexity of the flow-performance relationship identified empirically by Ippolito (1992), and Sirri and Tufano (1998). 8 This relationship is generally regarded as an exogenous feature of the interaction between mutual funds and their investors, and is typically interpreted as evidence that investors contribute enthusiastically to funds that have performed well, but hesitate to withdraw their investments from funds that have performed poorly.…”
Section: G the Relationship Between The Investor's Allocation And Idsupporting
confidence: 54%
“…Explicitly, several papers including Gruber (1996), Malkiel (1995), Carhart (1997), Sirri and Tufano (1998), Harless and Peterson (1998), Wermers (2000), Wermers (2003), Christoffersen and Musto (2002), Hortacsu and Syverson (2004), Kuhnen (2005), Gil-Bazo and Ruiz-Verdú (2009) have provided evidence of a puzzling negative relationship between advisory fees and mutual fund (gross or net) performance. This evidence has awkward economic implications, since it is incompatible with even the most charitable interpretation of investor rationality as it suggests that investors are willing to pay aboveaverage advisory fees to their underperforming managers.…”
mentioning
confidence: 99%
“…Obviously, only voluntary trading can be a reasonable proxy for overconfidence. Using total trading activity is particularly problematic in our context because there is ample evidence that past performance has a strong impact on fund flows (see, e.g., Sirri and Tufano, 1998) and we conjecture a positive impact of past performance on overconfidence, too. Consequently, the conjectured increase in trading activity after good performance might be driven by higher inflows and the need to invest this new money.…”
Section: Turnover Ratio As a Proxy For Overconfidencementioning
confidence: 92%
“…To take into account the time structure of the flows as exactly as possible, we start by calculating monthly flow figures based on the following method suggested by Sirri and Tufano (1998):…”
Section: Overconfidence and Past Performancementioning
confidence: 99%
“…In the mutual fund literature it is commonly found that the well performing funds attract much larger money- ‡ows than badly performing funds (see, e.g. Sirri and Tufano, 1998). A recent paper of Agarwal, Daniel and Naik (2003) reports similar …ndings for the hedge fund industry.…”
Section: Introductionmentioning
confidence: 89%